Design and development of a LIBS system on linear plasma device PSI-2 for in situ real-time diagnostics of plasma-facing materials. (August 2017) - Jiang, X.; Sergienko, G.; Schweer, B.; Gierse, N.; Hubeny, M.; Kreter, A.; Brezinsek, S.; Linsmeier, Ch.
Highlights: A LIBS system is build up on PSI-2 and a feasibility study of LIBS is performed. TEXTOR C first wall samples are studied by the LIBS system on PSI-2. In-situ real-time measurement of H/D content on W samples by LIBS is carried out in vacuum in the first 40–130 min after plasma exposure. Abstract: Laser induced breakdown spectroscopy (LIBS) is a strong candidate for detecting and monitoring the H/D/T content on the surface of plasma facing components (PFCs) due to its capability of fast direct in situ measurement in extreme environment (e.g., vacuum, magnetic field, long distance, complex geometry). To study the feasibilities and encounter the challenges of LIBS on plasma devices, a LIBS system has been set up on the linear plasma device PSI-2. A number of key parameters including laser energy, the influence of magnetic field and the persistence of laser induced plasma are studied. Real-time measurements of deuterium outgassing on tungsten samples exposed to deuterium plasma of 10 25 D/m 2 are performed in the first 40–130 min after plasma exposure. The experimental results are compared to the calculations in the literature.